Grandfathering or benchmarking: Which is more viable for the manufacturer’s low-carbon activities? - Wang, Zhanjie; Wang, Fei; Wang, Yongjian (Frontiers in Environmental Science, 2022)
Under the emissions trading policy, two typical carbon allowance allocation rules of the grandfathering and the benchmarking are widely adopted in the present carbon markets. Based on the mathematical modeling method, this paper explores which allocation rule is more viable for manufacturers’ low-carbon activities including abatement investment and remanufacturing activities. Meanwhile, the effects on total profit, total carbon emissions, consumer surplus and social welfare are discussed through numerical analysis. The results show that the benchmarking is more viable for manufacturers’ abatement investment activities than the grandfathering. Additionally, the benchmarking is always more viable for manufacturers’ remanufacturing activities only in a situation with a higher consumer low-carbon preference. Otherwise, which allocation rule is more beneficial to remanufacturing activities mainly depends on the abatement cost coefficient. Correspondingly, the higher the consumer low-carbon preference or the lower the abatement cost, the more viable the benchmarking is to achieve each performance target (e.g., total profit, emissions control, consumer surplus and social welfare). Based on these findings, this paper also recommends managerial insights for manufacturers and policy implications for policy-makers.